Production as translation: the merchant of Venice on the “foreign” stage - Susan L. Fischer (Ilha do Desterro)
In recent years, seventeenth-century classical drama has increasingly traversed national borders and become accessible to “foreign” audiences through modern productions based on translations and / or new versions that interrogate the original textual author-ity. The very act of translation, of denying a classical author such as Shakespeare his language, presents a challenge to the universalizing tendency of traditional stage history with its essentialist assumptions that classical texts “are stable and authoritative, that meaning is immanent in them, and that actors and directors are therefore interpreters rather than makers of meaning” (Bulman “Introd.” 1). In any reading of performance, whether past of present, the critic’s task is, as Cary Mazer reminds us, “an act of contextualizing, of historicizing, the performance in its cultural moment” (149).1 The performance text2 is itself historically contingent, the outcome of a process Patrice Pavis terms its “concretization,” wherein “signifier (literary work as thing), signified (aesthetic object), and Social Context.